A note on salience of own preferences and the consensus effect - Thomas Dohmen; Simone Quercia; Jana Willrodt (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
In this paper, we hypothesize that the strength of the consensus effect, i.e., the tendency for people to overweight the prevalence of their own values and preferences when forming beliefs about others' values and preferences, depends on the salience of own preferences. We manipulate salience by varying the order of elicitation of preferences and beliefs. Although our results confirm the existence of the consensus effect, we find no evidence of a difference between the two orders of elicitation. While our results highlight the robustness of the consensus effect, they also indicate that salience does not mediate the strength of this phenomenon
Keywords: C91; D01; D83; D91; 330; Consensus effect; social preferences; trust game; beliefs